Understanding continent-wide variation in vulture ranging behavior to assess feasibility of Vulture Safe Zones in Africa: Challenges and possibilities. (April 2022) - Kane, Adam; Monadjem, Ara; Aschenborn, H.K. Ortwin; Bildstein, Keith; Botha, André; Bracebridge, Claire; Buechley, Evan R.; Buij, Ralph; Davies, John P.; Diekmann, Maria; Downs, Colleen T.; Farwig, Nina; et al.
Abstract: Protected areas are intended as tools in reducing threats to wildlife and preserving habitat for their long-term population persistence. Studies on ranging behavior provide insight into the utility of protected areas. Vultures are one of the fastest declining groups of birds globally and are popular subjects for telemetry studies, but continent-wide studies are lacking. To address how vultures use space and identify the areas and location of possible vulture safe zones, we assess home range size and their overlap with protected areas by species, age, breeding status, season, and region using a large continent-wide telemetry datasets that includes 163 individuals of three species of threatened Gyps vulture. Immature vultures of all three species had larger home ranges and used a greater area outside of protected areas than breeding and non-breeding adults. Cape vultures had the smallest home range sizes and the lowest level of overlap with protected areas. Rüppell's vultures had larger home range sizes in the wet season, when poisoning may increase due to human-carnivore conflict. Overall, our study suggests challenges for the creation of Vulture Safe Zones to protect African vultures. At a minimum, areas of 24, 000 km 2 would be needed to protect the entire range of an adult African White-backed vulture and areas of more than 75, 000 km 2 for wider-ranging Rüppell's vultures. Vulture Safe Zones in Africa would generally need to be larger than existing protected areas, which would require widespread conservation activities outside of protected areas to be successful.